2010
DOI: 10.1136/jcp.2010.078634
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4aimmunostaining as an alternative to histology review for reliable grading of cervical intraepithelial lesions

Abstract: These data demonstrate that additive use of p16(INK4a) immunohistochemistry significantly improves the accuracy of grading CIN lesions by a single pathologist, equalling an expert consensus diagnosis. Hence, the authors advocate the combined use of p16(INK4a)-stained slides and conventional H&E sections in routine histopathology to improve accuracy of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 31 publications
3
59
0
1
Order By: Relevance
“…Nevertheless, due to the variation in immunohistochemistry assays and microscopic interpretation criteria, many studies have demonstrated a relationship between p16 overexpression and CIN3 (Tsoumpou et al, 2009). In the present study, p16 overexpression was significantly associated with the diffuse group rather than the focal group (P < 0.001), demonstrating a high sensitivity and specificity to diagnosis cervical premalignant lesions (Dijkstra et al, 2010). The HPV genotype (16 and 52 versus others) did not show a statistically significant correlation with p16 expression (P = 0.320), and independent of genotype, p16 expression was highlighted in the diffuse group.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, due to the variation in immunohistochemistry assays and microscopic interpretation criteria, many studies have demonstrated a relationship between p16 overexpression and CIN3 (Tsoumpou et al, 2009). In the present study, p16 overexpression was significantly associated with the diffuse group rather than the focal group (P < 0.001), demonstrating a high sensitivity and specificity to diagnosis cervical premalignant lesions (Dijkstra et al, 2010). The HPV genotype (16 and 52 versus others) did not show a statistically significant correlation with p16 expression (P = 0.320), and independent of genotype, p16 expression was highlighted in the diffuse group.…”
Section: Discussionsupporting
confidence: 53%
“…After that, the blades were set up with Entellan resin (Sigma-Aldrich ® , St. Louis, MO, USA). Distribution of p16 staining was scored as described by Dijkstra et al (2010), and representative focal, basal, diffuse, and diffuse full thickness staining are shown in Figure 1. We adapted and regrouped this rating for better evaluation where the negative, focal, and basal staining were considered focal and diffuse and diffuse full thickness staining were considered diffuse.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…A large number of biomarkers have been identified that are overexpressed in cervical cancer cells with potential for cervical cancer screening, such as p16 INK4A , Ki-67, Cyclin E, p53, and survivin, among others [5][6][7]. P16 INK 4A is a tumor suppressor protein which is induced in cells upon expression of high-risk HPV E7 protein [8] and several reports indicate that overexpression of p16 is associated with the process of carcinogenesis in the cervical epithelium [9].…”
Section: Introductionmentioning
confidence: 99%
“…Its use in conjunction with hematoxylin and eosin (H&E)-stained sections has substantially improved the interobserver agreement and diagnostic accuracy in the histopathologic evaluation of cervical biopsies. [8][9][10] Furthermore, there is evidence that detection of p16…”
mentioning
confidence: 99%
“…9,10 We hypothesized that it is likely that markers associated with proliferation can differentiate p16…”
mentioning
confidence: 99%